Solid: Enabler of decentralized, digital platforms ecosystems - Melanie Verstraete; Sofie Verbrugge; Didier Colle (International Telecommunications Society (ITS), 2022)
This paper studies the decentralized, digital ecosystem that is enabled by the Solid specification. Solid provides the possibility to break through data silos and simultaneously allows the end-user to regain control. However, research regarding business modelling and economic viability of such ecosystems is still lacking. Therefore, the goal of this paper is to provide first insights for this research area by proposing a value network model for such ecosystems. Though evaluation of existing frameworks and roles proposed by big initiatives like International Data Spaces, a first set of business roles is described. In a second step, these are evaluated with an actual validated use case where Solid is implemented within the HR domain.
Keywords: 330